Craniofacial fibrous dysplasia: Report of a case using computed tomographic scan diagnosis - Nikhil Diwan; Mahesh Chavan; Anagha Shete; Shivaji Khedkar (Wolters Kluwer Medknow Publications, 2013)
Fibro-osseous lesions are benign mesenchymal tumors in which mineralized tissue, blood vessels, and giant cells, in varying proportions, replace normal bone. Although this group of lesions includes reactive lesions, harmatomas, and neoplasms, they cannot be distinguished only on the basis of the histopathology which can only confirm their common fibro-osseous nature. Definitive diagnosis requires thorough radiological evaluation. Computed tomographic images of craniofacial fibrous dysplasia on bone windows may be helpful and allow precise pre-operative diagnosis and surgical planning.